ANALISIS KEPUASAN KERJA PEGAWAI STUDI KASUS DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA PEKANBARU - Kevin Odie Nugraha; Zulfadil Zulfadil; Taufiqurrahman Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in the Department of Population and Civil Registration Pekanbaru Jalan Mustafa Sari No. 1 Pekanbaru is the object of research is an employee of the Department of Population and Civil Registry of the city of Pekanbaru. In this study the authors used a descriptive approach where all the data gathered, interpreted and then connected with the theory with the theory that supports research on the study of literature. Analysis of the data in this study using a non-parametric statistical test analysis, a method of perceptionKeywords: Job Satisfaction